MANAJEMEN KONFLIK DALAM ORGANISASI - Alfrits B Tumiwa (Universitas Trisakti, 2005)
Conflict has been defined as the condition of objective of objective incompatibility between values or goal, as the behavior of delibertely interfering with another's goal achievement and emotionally in term of hostility. Conflict however can bring important benefit when it is handled skill fully. There are also some alternative solution in conflict management and finally conflict has some impact, like competency, work creatifity, and PTC.